2014
DOI: 10.1021/sc5003193
|View full text |Cite
|
Sign up to set email alerts
|

Bioderived “Green” Composite from Soy Protein and Eggshell Nanopowder

Abstract: A bio-derived and eco-friendly hybrid nanocomposite was developed from soy protein and eggshell nanopowder (ESNP). ESNP was synthesized via size reduction of chicken eggshells using ball milling followed by sonochemical process. Transmission electron microscopy and X-ray diffraction (XRD) studies revealed calcite particles in ESNP with size ranging between 20 and 40 nm. A trace of protein with as-synthesized ESNP was detected through X-ray photon spectroscopy (XPS) observation. Dispersion of ESNP in water was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 36 publications
(89 reference statements)
9
55
0
4
Order By: Relevance
“…For neat epoxy resin, many layered structures or sharp cracks can be seen in Figure 7a. Many studies have reported this appearance to be the distinctive brittle fracture surface of thermoset resins [43,44]. However, after adding ERFs to epoxy resins, the resins decrease in brittle features and sharp crests on the fracture surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…For neat epoxy resin, many layered structures or sharp cracks can be seen in Figure 7a. Many studies have reported this appearance to be the distinctive brittle fracture surface of thermoset resins [43,44]. However, after adding ERFs to epoxy resins, the resins decrease in brittle features and sharp crests on the fracture surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Figure (a,b) shows the ATR‐FTIR spectra of as‐synthesized and coated nEHA. Both spectra contain the characteristic peaks at 1091, 1026, 962, 610, and 560 cm −1 for phosphate stretching vibration modes (υ 3, υ 3, υ 1, υ 4 , and υ 2 of PO 4 − , respectively) . The band at 1450 cm −1 is from dissolved CO 2 during the wet chemical synthesis of nEHA which was liberated during the NaPA adsorption process in nEHA .…”
Section: Resultsmentioning
confidence: 99%
“…It is, in fact, the prime inorganic constituent (65–70%) of bone and hard tissue matrix that is indirectly bound to collagen through some noncollagenous proteins such as osteocalcin, osteopontin, or osteonectin in nanocrystal form . It has two binding sites, Ca 2+ and PO 4 − , which possess affinity toward biological macromolecules such as proteins . Synthetic HA has attracted much attention as a reinforcing material in biomedical applications because of its excellent functional properties including biocompatibility, osteoconductivity, nontoxicity, and bioactivity .…”
Section: Introductionmentioning
confidence: 99%
“…Soymeal is readily available in large quantities with annual production of around 172 million metric tons, low cost ($0.18-0.25 per lb) and good biodegradability as a coproduct from edible oil and bio-diesel production (Xu and Hanna 2009;Robert et al, 2014). Soymeal has been used as fillers or extenders of plastics (Wang et al, 1996), plywood bonding agent (Kumar et al, 2002), additives or coating of paper (Selling et al, 2013;Arboleda et al, 2014;Salam et al, 2015) and protein-based composites (Matthews et al, 2011;Khansari et al, 2013;Rahman et al, 2014) or scaffolds for tissue engineering (Huang et al, 2012;Zhao et al, 2014). However, consumption of soymeal in the above application areas could be low.…”
Section: Introductionmentioning
confidence: 99%